Analysis of Marketing Strategy as a Business Competition Strategy in SMES: a Study on achieved.co - Diki Egie Nugraha; Fadhilah Nur Oktaviani; Dwi Andre Vebriansyah; Sudarmiatin Sudarmiatin (Jurnal Bintang Manajemen, 2024)
In the era of the global economy and increasingly intense competition in Industry 4.0, Micro, Small, and Medium Enterprises (MSMEs) are required to continuously innovate to remain competitive. This study highlights the application of segmentation, targeting, and positioning (STP) strategies and the use of the marketing mix by Achieved.co. The research used a descriptive qualitative approach, with interviews as the primary data collection method. The results of this study reveal that Co's success in maintaining its presence amid intense competition was achieved through the implementation of effective marketing strategies. The segmentation process was based on geographical, demographic, and psychographic factors, primarily focusing on the Gen-Z demographic. Targeting was directed at consumers who value uniqueness and product innovation at affordable prices. Achieved. Co's positioning is strengthened through unique services such as customizable orders and offering specialized design services, although it does not yet have a specific slogan. This study underscores the importance of in-depth market analysis to enhance the competitiveness of MSMEs, particularly through the implementation of well-planned STP strategies and a structured marketing mix.